2020
DOI: 10.1098/rsif.2019.0804
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional wing structure attenuates aerodynamic efficiency in flapping fly wings

Abstract: The aerial performance of flying insects ultimately depends on how flapping wings interact with the surrounding air. It has previously been suggested that the wing's three-dimensional camber and corrugation help to stiffen the wing against aerodynamic and inertial loading during flapping motion. Their contribution to aerodynamic force production, however, is under debate. Here, we investigated the potential benefit of three-dimensional wing shape in three different-sized species of flies using models o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 58 publications
(97 reference statements)
2
30
0
Order By: Relevance
“…In corrugated wings of gliding dragonflies, slowly rotating vortices only develop at small angles of attack but flow broadly separates from the wing surface at larger angles (Re = 34,000 [ 53 ], Re = 1400 [ 136 ]). By contrast, a recent numerical study on root-flapping wings shows that corrugation valleys in fruit flies, house flies, and blowflies are unable to trap vortices at Reynolds numbers up to 1623 ( Figure 5 ) [ 83 ]. Thus, small-scale corrugation, low Reynolds number, spanwise flow advecting vorticity and high angle of attack make vortex trapping less likely in flapping insect wings.…”
Section: Functional Relevance Of Three-dimensional Wing Shapementioning
confidence: 98%
See 4 more Smart Citations
“…In corrugated wings of gliding dragonflies, slowly rotating vortices only develop at small angles of attack but flow broadly separates from the wing surface at larger angles (Re = 34,000 [ 53 ], Re = 1400 [ 136 ]). By contrast, a recent numerical study on root-flapping wings shows that corrugation valleys in fruit flies, house flies, and blowflies are unable to trap vortices at Reynolds numbers up to 1623 ( Figure 5 ) [ 83 ]. Thus, small-scale corrugation, low Reynolds number, spanwise flow advecting vorticity and high angle of attack make vortex trapping less likely in flapping insect wings.…”
Section: Functional Relevance Of Three-dimensional Wing Shapementioning
confidence: 98%
“…There is a wide variety of aspect ratios found in insect wings ranging from approximately 1.5 to 5.8 [ 118 , 119 , 120 , 121 , 122 ]. In Diptera, previous studies reported aspect ratios of 2.91–3.14 for Drosophila [ 121 , 122 ], 2.88 for Musca [ 83 ], and 2.62–2.93 for Calliphora [ 119 , 121 ]. The highest aerodynamic forces in hovering, root-flapping insect-like wings are produced at an aspect ratio of approximately 3.0 [ 123 ].…”
Section: The Aerodynamic Benefits Of An Ideal Planformmentioning
confidence: 99%
See 3 more Smart Citations